A carbon-based organic solvent filter membrane, a preparation method and application thereof

CN122974158APending Publication Date: 2026-10-27WESTLAKE UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611403974.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]本发明旨在解决现有有机溶剂纳滤膜耐溶剂性不足,以及碳基纳滤膜难以兼顾高通量与高选择性的问题,提供一种碳基有机溶剂纳滤膜及其制备方法和应用

Benefits of technology

(1)致密选择层由碳纳米管薄膜表层原位转化形成,无需额外沉积二维片层,可减少片层进入支撑层孔道造成的堵塞以及复合界面剥离问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974158A_ABST
    Figure CN122974158A_ABST
Patent Text Reader

Abstract

The application discloses a carbon-based nanofiltration membrane and a preparation method and application thereof. The carbon-based nanofiltration membrane has a dense selection layer with a depth of not more than 100 nm along the membrane thickness direction on the surface, and a porous carbon nanotube network support layer below the dense selection layer. The dense selection layer and the support layer are integrally formed and have a continuous transition interface therebetween. According to the carbon-based nanofiltration membrane, the dense selection layer is formed by in-situ conversion of the surface layer of the carbon nanotube film, without additional deposition of two-dimensional sheet layers, so that the problems of blockage caused by sheet layers entering the support layer channels and composite interface peeling can be reduced. The dense layer formed by in-situ conversion can significantly reduce the thickness while keeping the selection layer continuous and dense, thereby shortening the solvent transmission distance, reducing the tortuosity of the transmission path and the mass transfer resistance. The continuous transition structure between the dense selection layer and the support layer is stable in interface combination and is not prone to cracking, peeling or falling off in the process of pressure driving or solvent soaking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of membrane separation and nanofiltration technology, specifically relating to a carbon-based nanofiltration membrane, its preparation method, and its application. Background Technology

[0002] Organic solvents are widely used in chemical, pharmaceutical, food, coating, and fine chemical preparation industries. However, traditional organic solvent separation and purification processes heavily rely on heat-driven separation technologies such as distillation and extraction, which typically involve phase change processes and consume enormous amounts of energy. Statistics show that phase change-based organic solvent separation and purification processes, such as distillation, account for approximately 80% of total separation energy consumption; globally, industrial separation processes account for 10%–15% of total global energy consumption. Furthermore, traditional separation processes suffer from significant solvent loss, low recovery rates, and the potential introduction of tertiary components that contaminate the products. Therefore, there is an urgent need to develop a green, efficient, and low-energy-consumption alternative technology for organic solvent separation.

[0003] Membrane separation technology is widely recognized as one of the most energy-efficient separation technologies due to its outstanding advantages such as no phase change, low energy consumption, high separation efficiency, simple operation, and minimal environmental pollution. In recent years, membrane separation technology for organic solvents has been extensively developed. Among them, organic solvent nanofiltration (OSN), as a novel membrane separation technology, can efficiently separate organic solvents from solutes with a relative molecular mass of 200-1000 at room temperature and low pressure, showing great application potential in solvent recovery, drug concentration and purification, and catalyst recovery.

[0004] However, existing membrane separation materials still face many challenges. On the one hand, traditional reverse osmosis membranes and polymer membranes, such as microfiber membranes, are mostly designed for aqueous systems. When directly applied to organic solvent systems, the organic solvents can easily cause the membrane structure to swell or even break down, resulting in a loss of its original separation performance and structural integrity. On the other hand, even some commercially available solvent-resistant nanofiltration membranes generally suffer from thick separation layers and low solvent flux. When separating organic solvents, there is often a "trade-off" effect (i.e., a trade-off between selectivity and permeability) between the rejection rate of target molecules and the solvent flux, making it difficult to achieve both simultaneously.

[0005] For example, CN115888429A discloses a carbon-based nanofiltration membrane and its preparation and application. This carbon-based nanofiltration membrane includes an organic ultrafiltration base membrane and a membrane surface active layer. The membrane surface active layer is attached to the organic ultrafiltration base membrane (1). The membrane surface active layer is a modified graphene oxide sheet, and the organic ultrafiltration base membrane is polyethersulfone. The precursor of the membrane surface active layer is prepared and then attached to the organic ultrafiltration base membrane. That is, the organic ultrafiltration base membrane and the membrane surface active layer are prepared separately and finally combined together. CN115888432B discloses a carbon-based nanofiltration membrane and its preparation method and application. It also forms the final carbon-based nanofiltration membrane by physically combining the base membrane and graphene oxide. It has an unavoidable defect, that is, when the surface active layer and the base membrane are combined, it is easy to cause blockage of the pores of the base membrane or insufficient adhesion of the surface active layer, which is easy to fall off over time, resulting in insufficient filtration efficiency or service life.

[0006] Therefore, there is an urgent need to develop a new method for preparing nanofiltration membranes to obtain membrane materials that simultaneously possess high selectivity and high flux, thereby meeting the practical requirements for efficient separation of organic solvents. Summary of the Invention

[0007] To address the problems existing in the prior art, the present invention aims to provide a carbon-based organic solvent filter membrane, its preparation method, and its application, with the goal of improving the trade-off between selectivity and permeability.

[0008] This invention aims to address the problems of insufficient solvent resistance in existing organic solvent nanofiltration membranes and the difficulty in achieving both high flux and high selectivity in carbon-based nanofiltration membranes, and provides a carbon-based organic solvent nanofiltration membrane, its preparation method, and its applications.

[0009] The technical solution adopted in this invention is as follows: A carbon-based nanofiltration membrane has a dense selective layer on its surface with a depth of no more than 100 nm along the membrane thickness direction, and a porous carbon nanotube network support layer below the dense selective layer. The dense selective layer and the support layer are integrally formed and have a continuous transition interface between them.

[0010] Preferably, the carbon-based nanofiltration membrane is composed of carbon nanotubes.

[0011] Preferably, the carbon nanotubes are selected from single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes, and mixtures thereof.

[0012] Preferably, the carbon-based nanofiltration membrane has a thickness of 1 to 10 µm.

[0013] Preferably, the depth of the dense selective layer is 2 to 80 nm.

[0014] It consists of graphene oxide nanoribbon structures with a length of 5 to 30 µm.

[0015] Preferably, the molecular weight cutoff of the dense selective layer is not less than 320 Daltons.

[0016] According to another aspect of the present invention, another object of the present invention is to provide a method for preparing the carbon-based nanofiltration membrane, comprising the following steps: performing in-situ treatment on the surface of a porous carbon nanotube membrane, thereby opening the tubular structure of the carbon nanotubes in situ, forming a dense selective layer with a depth of no more than 100 nm along the thickness direction on the surface of the porous carbon nanotube membrane, thereby forming the final carbon-based nanofiltration membrane.

[0017] Preferably, the in-situ processing method includes, but is not limited to, liquid phase chemical oxidation, plasma etching, catalytic cutting of metal nanoparticles, and laser irradiation unwinding.

[0018] Preferably, in the liquid-phase chemical oxidation method, the carbon nanotube membrane is pretreated by immersing it in concentrated sulfuric acid for 15 min to fully wet the carbon nanotube membrane. Then, the carbon nanotube membrane is transferred to an oxidation reaction solution composed of potassium permanganate and an acidic reaction medium, and an in-situ oxidation reaction is carried out at a set temperature.

[0019] Preferably, the mass ratio of potassium permanganate to carbon nanotubes is 3:1 to 7:1, more preferably 4:1 to 5:1; the reaction temperature is 50 to 75 °C, more preferably 55 to 70 °C, and even more preferably 60 to 65 °C; the reaction time is 15 to 600 min, more preferably 120 to 500 min, and even more preferably about 480 min.

[0020] Preferably, the acidic reaction medium is selected from concentrated sulfuric acid with a mass percentage concentration of 98%, or a combination of sulfuric acid with a mass percentage concentration of 98% and phosphoric acid with a mass percentage concentration of 85%.

[0021] Preferably, when the acidic reaction medium is a combination of sulfuric acid and phosphoric acid, the volume ratio of sulfuric acid to phosphoric acid is 1:0 to 1:1, preferably 9:1. The addition of phosphoric acid can, to some extent, regulate the oxidation reaction rate and reduce the risk of excessive oxidation and structural damage to the carbon nanotube membrane.

[0022] Preferably, in the plasma etching method, the in-situ treatment of one side surface of the carbon nanotube film is carried out as follows: the carbon nanotube film is placed in a plasma treatment device, and the surface of the carbon nanotube film is treated with oxygen-containing plasma generated by oxygen, air, water vapor, carbon dioxide, or a combination thereof. By adjusting the plasma power, treatment time, gas composition, and gas pressure, the carbon nanotubes on the film surface undergo controlled oxidation and partial deconstruction, forming a gradient structure with a gradually decreasing degree of oxidation along the film thickness direction.

[0023] Preferably, the plasma-treated carbon nanotube film can be further subjected to heat treatment in concentrated sulfuric acid or a mixture of sulfuric acid and phosphoric acid to promote further deconstruction of the surface carbon nanotubes and introduction of oxygen-containing functional groups. The acid treatment is an optional step.

[0024] In the carbon-based nanofiltration membrane preparation method according to the present invention, during the in-situ oxidation process, the oxidant first contacts the carbon nanotubes on the surface of the carbon nanotube membrane, causing the surface carbon nanotubes to partially deconstruct and / or unfold along the axial direction, and forming overlapping and / or partially stacked graphene oxide nanoribbons in situ. As the dense surface structure gradually forms, the further transport of the oxidation reaction solution into the membrane interior is restricted, causing the degree of oxidation to gradually decrease along the membrane thickness direction. Thus, a dense selective layer is formed on the membrane surface, with a porous carbon nanotube network retained below as a support layer, and a continuous transition region formed between the two.

[0025] By adjusting the amount of potassium permanganate, the reaction temperature, and the reaction time, the degree of oxidation and deconstruction of carbon nanotubes can be controlled. Under suitable conditions, oxygen-containing functional groups can be introduced onto the membrane surface while maintaining the integrity of the overall membrane structure, forming a selective layer of graphene oxide nanoribbons with nanoscale transport channels.

[0026] The porous carbon nanotube membrane can be prepared by conventional methods, as long as the conventional methods can obtain the porous carbon nanotube membrane with the performance requirements of this disclosure, and there are no particular limitations. For example, it can be prepared by chemical vapor deposition, floating catalyst chemical vapor deposition, vacuum filtration, pressure filtration, blade coating, spray coating, spin coating or Langmuir-Blodgett method.

[0027] More specifically, taking vacuum filtration as an example, the porous carbon nanotube membrane can be prepared as follows: 1) Carbon nanotubes were added to a solvent and pre-dispersed under stirring to obtain a carbon nanotube dispersion; 2) The carbon nanotube dispersion obtained in step 1) is filtered onto the surface of the AAO filter membrane using vacuum filtration. After the membrane surface is free of obvious solvent residue, it is washed and filtered until the membrane is basically dry. Then the carbon nanotube membrane is peeled off from the surface of the AAO filter membrane to obtain a porous carbon nanotube membrane formed by the overlapping of carbon nanotubes.

[0028] According to another aspect of the invention, another object of the invention is to provide the application of the carbon-based nanofiltration membrane in the separation or purification of organic solvent systems.

[0029] Preferably, the carbon-based nanofiltration membrane can be used for solute separation, solvent recovery, solvent replacement, solute concentration, and solute purification in organic solvent systems, especially for the separation and purification of peptides, active pharmaceutical ingredients, pharmaceutical intermediates, oligomers, dyes, catalysts, and natural products. During peptide separation, the peptide can be retained in the retentate while at least one of inorganic salts, organic solvents, and small molecule impurities enters the permeate, thereby achieving peptide desalting, concentration, solvent replacement, or purification.

[0030] Beneficial effects Compared with the prior art, the present invention has at least the following beneficial effects: (1) The dense selective layer is formed by in-situ transformation of the surface of the carbon nanotube film, without the need for additional deposition of two-dimensional sheets, which can reduce the blockage caused by the sheets entering the pores of the support layer and the problem of composite interface peeling.

[0031] (2) In-situ oxidation can significantly reduce the thickness of the selective layer while maintaining its continuity and density, and shorten the solvent transport distance, reduce the tortuosity of the transport path and the mass transfer resistance.

[0032] (3) The lower carbon nanotube porous network can maintain high porosity and good support performance, which is conducive to obtaining high solute retention performance and organic solvent flux at the same time.

[0033] (4) The dense selective layer and the support layer have a continuous transition structure, and the interface is stable, making it less prone to cracking, peeling or falling off during pressure driving or solvent immersion.

[0034] (5) The obtained filter membrane is mainly composed of carbon materials and has good structural stability to organic solvents and acidic and alkaline media, making it suitable for separation processes in complex chemical environments. Attached Figure Description

[0035] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0036] Figure 1 This is a microstructure diagram of the surface-dense graphene oxide nanoribbon selective layer formed by in-situ oxidation treatment of the carbon nanotube film obtained according to Example 1.

[0037] Figure 2 This is a microstructure diagram of the porous carbon nanotube support layer inside the carbon-based nanofiltration membrane obtained according to Example 1.

[0038] Figure 3This is a cross-sectional microstructure diagram of the gradient structure of the carbon-based nanofiltration membrane obtained according to Example 1, which shows a continuous transition from a dense selective layer to a porous support layer along the membrane thickness direction.

[0039] Figure 4 Based on the XPS elemental composition analysis results of the carbon-based nanofiltration membrane obtained in Example 1 at different depths along the membrane thickness direction, the trend of oxygen content gradually decreasing from the membrane surface to the membrane interior is shown.

[0040] Figure 5 The results are based on Raman spectral analysis at different depths along the thickness direction of the carbon-based nanofiltration membrane obtained in Example 1.

[0041] Figure 6 This is a comparison of the retention performance of the carbon-based nanofiltration membrane obtained in Example 1 for dyes of different molecular weights.

[0042] The present invention will now be described in detail. Before proceeding with the description, it should be understood that the terminology used in this specification and the appended claims should not be construed as limited to its general or dictionary meaning, but rather should be interpreted according to the meaning and concept corresponding to the technical aspects of the invention, based on the principle that the inventors are allowed to appropriately define the terms for the best interpretation. Therefore, the description presented herein is merely a preferred example for illustrative purposes and is not intended to limit the scope of the invention. It should be understood that other equivalents or modifications can be obtained from it without departing from the spirit and scope of the invention.

[0043] In this document, the terms “comprising,” “including,” “having,” “containing,” or any other similar terms are open-ended conjunctions intended to cover non-exclusive inclusions. For example, a composition or article containing a plurality of elements is not limited to those listed herein, but may also include other elements not explicitly listed but typically inherent to the composition or article. Furthermore, unless explicitly stated to the contrary, the term “or” is inclusive, not exclusive. For example, the condition “A or B” is satisfied in any of the following cases: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); A and B are both true (or exist). Moreover, in this document, the terms “comprising,” “including,” “having,” and “containing” should be interpreted as specifically disclosed and simultaneously cover closed or semi-closed conjunctions such as “composed of” and “substantially composed of.”

[0044] In this application, the use of terms such as “preferred,” “advantageous,” and similar expressions implies that the features following them will be beneficial to the purposes of this invention.

[0045] Unless otherwise specified, all numerical values ​​representing quantities of ingredients, etc., used in the specification and claims should be understood to be modified by the term "approximately". Therefore, unless indicated to the contrary, the numerical values ​​and parameters described herein are approximate values ​​that can be varied as needed for the desired purpose.

[0046] In this document, all features or conditions defined in the form of numerical ranges or percentage ranges are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible secondary ranges and individual values ​​within those ranges, particularly integer values. For example, a range description of "1 to 8" should be considered as specifically disclosing all secondary ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., particularly secondary ranges defined by all integer values, and should be considered as specifically disclosing individual values ​​within those ranges such as 1, 2, 3, 4, 5, 6, 7, 8, etc. Unless otherwise specified, the foregoing interpretation applies to all content throughout this invention, regardless of its scope.

[0047] If a quantity or other numerical value or parameter is expressed as a range, a preferred range, or a series of upper and lower limits, it should be understood that this document has specifically disclosed all ranges consisting of any upper or preferred value of that range and the lower or preferred value of that range, regardless of whether such ranges are separately disclosed. Furthermore, when a range of numerical values ​​is mentioned herein, unless otherwise stated, the range shall include its endpoints and all integers and fractions within the range.

[0048] In this document, numerical values ​​are to be understood as having a precision with significant digits, provided that the purpose of the invention can be achieved. For example, the number 40.0 should be understood to cover a range from 39.50 to 40.49.

[0049] In addition, unless otherwise stated, the reagents and solvents disclosed below were sourced as follows: SWCNT was purchased from Tuball; m-cresol (60 mL) was purchased from Sigma-Aldrich; AAO template (47 mm diameter, 0.2 μm pore size) was purchased from Whatman / GE; potassium permanganate was purchased from Sinopharm Chemical Reagent Co., Ltd.; hydrogen peroxide solution (6%) was purchased from Fisher Scientific; and dyes were purchased from Aladdin Reagent (Shanghai) Co., Ltd. Advanced ultrasonic treatment was performed using a Qsonica Sonicators Q125 ultrasonic disruptor; visible and near-infrared rapid imaging confocal Raman spectroscopy was measured using a confocal Raman spectrometer from WITec GmbH, Germany; ultraviolet-visible spectroscopy was measured using an Analytik Jena S600 ultraviolet-visible spectrophotometer; AFM was measured using a Park F40 atomic force microscope; SEM was measured using a Thermo Fisher Scientific Phenom Pharos G2 scanning electron microscope; and vacuum plasma cleaning was performed using a LEBO Science PT1000 vacuum plasma cleaner.

[0050] The porous carbon nanotube membrane in the preparation method of the carbon-based nanofiltration membrane according to the present invention can be prepared as follows: Single-walled carbon nanotubes are added to m-cresol at room temperature and pre-dispersed for 1 h under stirring in a homogenizer to obtain an initial carbon nanotube dispersion. Subsequently, the initial dispersion is placed in a probe-type ultrasonic device and ultrasonically treated in pulse mode for 30 min to obtain a uniformly dispersed carbon nanotube / m-cresol dispersion.

[0051] Take 100 mL of a 0.2 mg / mL carbon nanotube / m-cresol dispersion, containing 20 mg of carbon nanotubes, and filter it onto the surface of an AAO filter membrane using a vacuum filtration device. After no obvious m-cresol residue remains on the membrane surface, wash with 10 mL of ethanol each time, for a total of 3 washes. Continue filtration until the membrane is basically dry, then peel the carbon nanotube membrane off the surface of the AAO filter membrane to obtain a continuous porous carbon nanotube membrane formed by the overlapping of carbon nanotubes.

[0052] Membrane performance evaluation This disclosure describes the nanofiltration performance (permeability and selectivity) of prepared carbon nanotube membranes and heterogeneous carbon nanotube membranes using a vacuum dead-end filtration method at approximately 1 bar pressure. Each performance evaluation result is derived from the average of data from at least three samples, and the error is calculated based on the standard deviation. Flux is defined as the volume of liquid passing through the membrane per unit volume per unit time, and is defined by the following equation:

[0053] Where V represents the volume of filtrate collected, A is the effective membrane area, and t is the filtration time. P represents the applied pressure.

[0054] Retention rate is usually expressed as the ratio of solute concentration in the permeate to solute concentration in the injection sample, where the solute concentration is measured by a UV-Vis spectrometer.

[0055] The solute used in this disclosure is methylene blue.

[0056] The following embodiments are merely examples illustrating implementations of the present invention and do not constitute any limitation on the present invention. Those skilled in the art will understand that modifications made without departing from the spirit and concept of the present invention fall within the protection scope of the present invention. Unless otherwise specified, the reagents and instruments used in the following embodiments are commercially available products.

[0057] Example 1: Preparation of carbon-based nanofiltration membranes by wet chemical in-situ oxidation Single-walled carbon nanotubes were added to m-cresol at room temperature and pre-dispersed for 1 h under stirring in a homogenizer to obtain an initial carbon nanotube dispersion. Subsequently, the initial dispersion was placed in a probe-type ultrasonic device and ultrasonically treated in pulse mode for 30 min to obtain a uniformly dispersed carbon nanotube / m-cresol dispersion.

[0058] Take 100 mL of a 0.2 mg / mL carbon nanotube / m-cresol dispersion, containing 20 mg of carbon nanotubes, and filter it onto the surface of an AAO filter membrane using a vacuum filtration device. After the membrane surface is free of obvious m-cresol residue, wash it with 10 mL of ethanol each time, for a total of 3 washes. Continue filtration until the membrane is basically dry, and then peel the carbon nanotube membrane off the surface of the AAO filter membrane to obtain a continuous porous carbon nanotube membrane formed by the overlapping of carbon nanotubes.

[0059] The carbon nanotube membrane was pretreated by immersing it in 98% concentrated sulfuric acid for 15 min, then removed and placed in 4 mL of potassium permanganate-concentrated sulfuric acid oxidation reaction solution. The reaction solution contained 16 mg of potassium permanganate and 4 mL of concentrated sulfuric acid.

[0060] The reaction system was heated to 60 °C and reacted for 4 h. After the reaction was completed, the membrane was cooled to room temperature and transferred to a stop solution prepared by 1 mL of 30% hydrogen peroxide solution and 100 mL of ice-cold deionized water, and soaked for 15 min.

[0061] The membrane after the reaction was supported and transferred using a flat filter membrane. It was then thoroughly washed with deionized water and ethanol in sequence, and then allowed to dry naturally. The resulting membrane was then peeled off from the supporting filter membrane to obtain a carbon-based nanofiltration membrane.

[0062] After in-situ oxidation, some carbon nanotubes on the surface of the resulting film undergo axial deconstruction and / or unfolding, further forming an overlapping and partially stacked network of graphene oxide nanoribbons, thereby constructing a dense selective layer on the film surface. Figure 1 The carbon nanotubes inside the membrane largely retain their original one-dimensional tubular morphology and interconnected porous network structure, forming a support layer with high porosity. Figure 2 ).

[0063] Furthermore, the dense selective layer and the porous support layer are not a simple layered composite structure with a clear interface, but rather exhibit a gradient structure that gradually transitions from the surface to the interior of the film. Figure 3 XPS depth profiling results showed that the oxygen content gradually decreased as the test depth increased from the film surface to the interior, and no obvious abrupt interface was observed, indicating that the oxidation degree of carbon nanotubes continuously weakened along the film thickness direction. Figure 4 Meanwhile, Raman depth characterization showed that the (ID / IG) ratio, which characterizes defects and edge structures in carbon materials, also changed continuously from the film surface to the interior with varying test locations. Figure 5 The results corroborate the XPS findings. These results indicate that in-situ oxidative unzipping does not form an oxide layer independent of the substrate on the carbon nanotube film surface. Instead, it causes the degree of deconstruction and oxidation of the carbon nanotubes to gradually decrease from the film surface to the interior, thereby forming a gradient structure that continuously transitions from a dense graphene oxide nanoribbon selective layer to a porous carbon nanotube support layer.

[0064] The carbon nanotubes on the surface of the resulting film undergo in-situ oxidation, resulting in axial deconstruction and / or unfolding, forming a dense selective layer containing graphene oxide nanoribbons. Figure 1 The underlying carbon nanotubes maintain an overlapping porous network structure, forming a support layer. Figure 2 The selection layer and the support layer have a continuous transition structure.

[0065] Using the aforementioned vacuum dead-end filtration method, the solvent flux and solute rejection of the obtained carbon-based nanofiltration membrane were tested at a transmembrane pressure of approximately 1 bar.

[0066] Comparative Example 1: Carbon nanotube membranes without in-situ oxidation Single-walled carbon nanotubes were added to m-cresol at room temperature and pre-dispersed using a homogenizer for 1 h. The initial dispersion was then placed in a probe-type ultrasonic device and sonicated in pulse mode for 30 min to obtain a carbon nanotube / m-cresol dispersion with a concentration of 0.2 mg / mL.

[0067] Take 100 mL of the dispersion containing 20 mg of carbon nanotubes and filter it onto the surface of the AAO filter membrane using a vacuum filtration device. After the obvious m-cresol residue disappears, wash with 10 mL of ethanol each time, for a total of 3 washes. Continue filtration until the membrane is dry, and then peel the carbon nanotube membrane off the AAO filter membrane to obtain a carbon nanotube membrane without in-situ oxidation treatment.

[0068] The solvent flux and solute rejection of the obtained carbon nanotube membrane were tested under the same conditions as in Example 1.

[0069] Comparative Example 2: Carbon nanotube membranes treated only with concentrated sulfuric acid Carbon nanotube membranes were prepared according to the method of Comparative Example 1. The obtained carbon nanotube membranes were immersed in concentrated sulfuric acid and treated at 60 °C for 4 h. After treatment, the membranes were cooled to room temperature and thoroughly washed with deionized water until the washing solution was nearly neutral. The membranes were then dried to obtain the control membranes treated only with concentrated sulfuric acid.

[0070] The solvent flux and solute rejection of the comparison membrane were tested under the same conditions as in Example 1.

[0071] Comparative Example 3: Carbon-based nanofiltration membrane prepared by secondary filtration Single-walled carbon nanotubes were added to m-cresol at room temperature and pre-dispersed for 1 h under stirring in a homogenizer to obtain an initial carbon nanotube dispersion. Subsequently, the initial dispersion was placed in a probe-type ultrasonic device and ultrasonically treated in pulse mode for 30 min to obtain a uniformly dispersed carbon nanotube / m-cresol dispersion.

[0072] Take 100 mL of a 0.2 mg / mL carbon nanotube / m-cresol dispersion, containing 20 mg of carbon nanotubes, and filter it onto the surface of an AAO filter membrane using a vacuum filtration device. After no obvious m-cresol residue remains on the membrane surface, wash with 10 mL of ethanol each time, for a total of 3 washes. Continue filtration until the membrane is basically dry to obtain a continuous porous carbon nanotube membrane formed by the overlapping of carbon nanotubes, which is retained on the surface of the AAO filter membrane for subsequent secondary filtration.

[0073] Single-walled carbon nanotubes were separately added to a concentrated sulfuric acid oxidation system containing potassium permanganate for oxidative decomposition treatment, causing the carbon nanotubes to destructure and / or unfold along the axial direction, yielding a reaction product containing graphene oxide nanoribbons. After the reaction was completed, the reaction was terminated with hydrogen peroxide, and the nanoribbons were repeatedly washed with deionized water to remove residual acid, oxidant, and manganese salt. The obtained graphene oxide nanoribbons were redispersed in deionized water and / or a suitable polar solvent to obtain a graphene oxide nanoribbon dispersion.

[0074] A certain volume of the above-mentioned graphene oxide nanoribbon dispersion was deposited onto the surface of a pre-prepared carbon nanotube membrane by vacuum filtration. The filtration quality of the graphene oxide nanoribbons was controlled to ensure that its surface loading was similar to that of the selective layer formed after in-situ oxidation in Example 1. After filtration, the membrane was washed sequentially with deionized water and ethanol, and filtration continued until the membrane was essentially dry. The resulting composite membrane was then peeled off from the AAO filter membrane surface to obtain a carbon-based nanofiltration membrane prepared by a secondary filtration method.

[0075] In the comparative example, the graphene oxide nanoribbons were pre-prepared and then loaded onto the surface of the carbon nanotube film by physical deposition. Therefore, a relatively clear physical composite interface is formed between the graphene oxide nanoribbon selective layer and the underlying carbon nanotube support layer, rather than a continuous transition structure formed by in-situ oxidation of the same carbon nanotube network.

[0076] The solvent flux and solute rejection rate of the obtained secondary filtration carbon-based nanofiltration membrane were tested under the same test conditions as in Example 1. Simultaneously, the membrane's operational stability was evaluated through continuous filtration and / or long-term solvent filtration tests, and changes in membrane flux, rejection rate, and selectivity layer structure before and after the tests were recorded.

[0077] In contrast, the graphene oxide nanoribbons in Example 1 are formed by in-situ deconstruction of the carbon nanotube membrane surface, forming a continuous gradient transition structure between the dense selective layer and the porous support layer. This is beneficial for obtaining a continuous and dense sieving region with a smaller selective layer thickness, while reducing internal pore blockage and interfacial transport resistance, and improving the structural stability of the selective layer during long-term filtration.

[0078] By comparing Example 1 and Comparative Example 1, the effect of in-situ oxidation to form a graphene oxide nanoribbon selective layer on membrane separation performance can be evaluated. By comparing Example 1 and Comparative Example 2, the effects of potassium permanganate oxidation and simple concentrated sulfuric acid treatment on membrane structure and separation performance can be distinguished. By comparing Example 1 and Comparative Example 3, the effect of the in-situ selective layer formation method on membrane separation performance and structural stability can be evaluated. Under similar selective layer composition and loading, the graphene oxide nanoribbons formed by secondary filtration mainly adhere to the surface of the carbon nanotube support layer through physical action, which easily leads to local accumulation, some nanoribbons entering the interior of the carbon nanotube network, and increased selective layer thickness, thereby increasing solvent transport resistance. In addition, there is a relatively clear interface between the selective layer and the support layer, which may lead to interface slippage, local detachment, or structural rearrangement under continuous pressure and solvent immersion conditions.

[0079]

[0080] Test Example 1: Permeation performance to different organic solvents The carbon-based nanofiltration membrane prepared in Example 1 was used to test the permeation performance of different solvents under a transmembrane pressure of approximately 1 bar using a dead-end filtration method. The results are shown in the table below.

[0081]

[0082] Test results show that the carbon-based nanofiltration membrane prepared in this invention exhibits excellent permeation performance for a variety of organic solvents with different polarities, molecular sizes, and viscosities. Specifically, the permeabilities for acetone, acetonitrile, and methanol reach 1243, 1057, and 751 L·m⁻¹, respectively. -2 ·h -1 ·bar -1 It also maintains high solvent transport capacity for organic solvents such as DMF, ethanol, and 1-propanol.

[0083] Test Example 2: Retention performance of different solutes The carbon-based nanofiltration membrane prepared in Example 1 was used to test its retention performance for solutes of different molecular weights under a transmembrane pressure of approximately 1 bar using a dead-end filtration method. The tested solutes included inorganic salts and organic dye molecules of different molecular weights. The results of the retention rate as a function of solute molecular weight are shown in the figure.

[0084] Test results show that for small-sized inorganic salts such as NaCl and Na₂SO₄, the membrane rejection rate is close to 0, indicating that these small-sized ions can easily permeate the selective layer of the membrane. As the solute molecular size increases, the membrane rejection rate rapidly increases. Specifically, for the solute labeled CS (Chrysoidine, Basic Orange, molecular weight 248.71), the rejection rate is approximately 68%; when the solute molecular weight further increases to approximately 320 Da and above, the rejection rate rapidly increases to over 99%. Figure 6 ).

[0085] For dye molecules with molecular weights of approximately 320–1298 Da, such as MB (Methylene Blue, molecular weight 319.85), BV (Basic Violet, molecular weight 365.91), AR (Acid Red, molecular weight 585.54), CBB (Coomassie Brilliant Blue, R-250, molecular weight 825.97), and AB (Alcian Blue, molecular weight 1298.86), the resulting carbon-based nanofiltration membranes all achieved retention rates exceeding 99.7%, exhibiting significant size sieving characteristics. Based on the retention curves of solutes with different molecular weights, the resulting membranes had a molecular weight cutoff (MWCO) of no less than 320 Da.

[0086] The above results demonstrate that the carbon-based nanofiltration membrane prepared in this invention can efficiently retain larger organic molecules with a molecular weight of approximately 320 Da or higher while maintaining high permeability to inorganic salts and other small-sized components. The in-situ formed graphene oxide nanoribbon network on the surface provides nanoscale selective transport channels and achieves effective retention of larger solutes through size sieving and interfacial interactions generated by oxygen-containing functional groups, while the underlying porous carbon nanotube network mainly provides rapid mass transfer channels and mechanical support.

[0087] Therefore, the membrane obtained by the present invention is particularly suitable for separation processes that require simultaneous "large molecule retention - small molecule or salt permeation", such as drug and peptide concentration, desalting, solvent replacement and small molecule impurity removal.

[0088] The above results demonstrate that this invention, by forming an ultrathin, dense selective layer in situ on the surface of a carbon nanotube membrane, achieves molecular sieving capabilities without significantly sacrificing the original rapid mass transfer capacity of the porous carbon nanotube network. In particular, the resulting membrane exhibits high solvent permeability for organic solvents commonly used in pharmaceutical and fine chemical processes, such as acetonitrile and methanol, indicating its potential application in processes such as organic solvent nanofiltration, solvent recovery, and solvent replacement.

[0089] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A carbon-based nanofiltration membrane having a dense selective layer with a depth of no more than 100 nm along the membrane thickness direction on its surface, wherein a porous carbon nanotube network support layer is located below the dense selective layer, the dense selective layer and the support layer are integrally formed, and there is a continuous transition interface between the two.

2. The carbon-based nanofiltration membrane according to claim 1, characterized in that, The carbon-based nanofiltration membrane is composed of carbon nanotubes; Preferably, the carbon nanotubes are selected from single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes, and mixtures thereof; Preferably, the carbon-based nanofiltration membrane has a thickness of 1 to 10 µm; Preferably, the depth of the dense selective layer is 2 to 80 nm; It is composed of graphene oxide nanoribbon structures, wherein the length of the nanoribbons is 5 to 30 µm; Preferably, the molecular weight cutoff of the dense selective layer is not less than 320 Daltons.

3. The method for preparing the carbon-based nanofiltration membrane according to claim 1 or 2, comprising the following steps: The surface of the porous carbon nanotube membrane is treated in situ to open the tubular structure of the carbon nanotubes in situ, forming a dense selective layer with a depth of no more than 100 nm along the thickness direction on the surface of the porous carbon nanotube membrane, thus forming the final carbon-based nanofiltration membrane.

4. The preparation method according to claim 3, characterized in that, The in-situ processing methods include liquid phase chemical oxidation, plasma etching, catalytic cutting of metal nanoparticles, and laser irradiation unwinding.

5. The preparation method according to claim 4, characterized in that, In the liquid-phase chemical oxidation method, the carbon nanotube membrane is pretreated by immersing it in concentrated sulfuric acid for 15 min to fully wet the carbon nanotube membrane. Then, the carbon nanotube membrane is transferred to an oxidation reaction solution composed of potassium permanganate and an acidic reaction medium, and an in-situ oxidation reaction is carried out at a set temperature. Preferably, the mass ratio of potassium permanganate to carbon nanotubes is 3:1 to 7:1, more preferably 4:1 to 5:1; the reaction temperature is 50 to 75 °C, more preferably 55 to 70 °C, and even more preferably 60 to 65 °C; the reaction time is 15 to 600 min, more preferably 120 to 500 min, and even more preferably about 480 min. Preferably, the acidic reaction medium is selected from concentrated sulfuric acid with a mass percentage concentration of 98%, or a combination of sulfuric acid with a mass percentage concentration of 98% and phosphoric acid with a mass percentage concentration of 85%. Preferably, when the acidic reaction medium is a combination of sulfuric acid and phosphoric acid, the volume ratio of sulfuric acid to phosphoric acid is 1:0 to 1:1, preferably 9:

1.

6. The preparation method according to claim 4, characterized in that, In plasma etching, one side of the carbon nanotube film is treated in situ as follows: The carbon nanotube film is placed in a plasma treatment device, and the surface of the carbon nanotube film is treated with oxygen-containing plasma generated by oxygen, air, water vapor, carbon dioxide or a combination thereof. By adjusting the plasma power, treatment time, gas composition and gas pressure, the carbon nanotubes on the film surface undergo controlled oxidation and partial deconstruction, and a gradient structure with a gradually decreasing degree of oxidation is formed in the film thickness direction.

7. The preparation method according to claim 6, characterized in that, Alternatively, the plasma-treated carbon nanotube film can be further heated in concentrated sulfuric acid or a mixture of sulfuric acid and phosphoric acid to promote further deconstruction of the surface carbon nanotubes and introduction of oxygen-containing functional groups.

8. The application of the carbon-based nanofiltration membrane according to claim 1 or 2 in the separation or purification of organic solvent systems.

9. The application according to claim 8, characterized in that, The carbon-based nanofiltration membrane can be used for solute separation, solvent recovery, solvent replacement, solute concentration and solute purification in organic solvent systems, and is preferably used for the separation and purification of peptides, active pharmaceutical ingredients, pharmaceutical intermediates, oligomers, dyes, catalysts and natural products.

Citation Information

Patent Citations

  • Carbon-based nanofiltration membrane as well as preparation and application thereof

    CN115888429A

  • A carbon-based nanofiltration membrane, its preparation method and application

    CN115888432B